2020
DOI: 10.1002/bit.27379
|View full text |Cite
|
Sign up to set email alerts
|

Differential fibrotic phenotypes of hepatic stellate cells within 3D liver organoids

Abstract: Liver fibrosis occurs in most cases of chronic liver disease, which are somewhat common, but also a potentially deadly group of diseases. In vitro modeling of liver fibrosis relies primarily on the isolation of in vivo activated hepatic stellate cells (aHSCs) and studying them in standard tissue culture dishes (two‐dimensional [2D]). In contrast, modeling of fibrosis in a biofabricated three‐dimensional (3D) construct allows us to study changes to the environment, such as extracellular matrix (ECM) composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…HepaRG+aHSC organoids showed fibers significantly longer and thicker than within HepaRG+LX-2 organoids ( Figure 3B). In a previous study we showed that a monoculture of aHSC cells created longer and thicker fibers than the monoculture of LX-2 cells [36]. Similar analysis of collagen fibers were carried out in healthy and cirrhotic liver specimens.…”
Section: Quantitative Analysis Of Collagen I Fibers In the Liver Orgasupporting
confidence: 52%
See 1 more Smart Citation
“…HepaRG+aHSC organoids showed fibers significantly longer and thicker than within HepaRG+LX-2 organoids ( Figure 3B). In a previous study we showed that a monoculture of aHSC cells created longer and thicker fibers than the monoculture of LX-2 cells [36]. Similar analysis of collagen fibers were carried out in healthy and cirrhotic liver specimens.…”
Section: Quantitative Analysis Of Collagen I Fibers In the Liver Orgasupporting
confidence: 52%
“…factors (TGF-β) associated with both fibrosis and development (Supplemental Figure 3), addition of ALK5i effectively reduced TGF-β gene expression [36].…”
Section: Accepted Articlementioning
confidence: 99%
“…Irreversible fibrosis results when the tissue microenvironment favors ECM production and deposition over degradation and remodeling. Analysis of collagen fiber parameters, such as length, width, angularity, and straightness, in normal and pathologic disease states may help unlock the conditions that favor irreversible fibrosis ( 40 , 43 , 44 , 46 ), and this method of evaluating collagen has been validated by Caetano et al as comparable to the gold standard hydroxyproline assay ( 45 ). Increased collagen fiber width in the tumor microenvironment is a powerful negative prognostic indicator associated with reduced 5-year survival that was validated in two separate gastric cancer cohorts of 225 and 151 cancer patients ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of 10 images were averaged for each cat ( N = 30) for further analysis. For tissues stained with Picrosirius Red under polarized light (PSR-POL), two collagen fiber analyses were performed: (1) Collagen fiber quantification for length and width using the segmentation software CT-FIRE (Laboratory for Optical and Computation Instrumentation, University of Wisconsin) ( 39 45 ) ( Figure 4B ); and (2) Hue analysis for level of collagen bundling and total collagen quantification using a MATLAB script (R2020a, MathWorks, Natick, MA) ( 43 , 44 , 46 ). Results of 10 images were averaged for each cat ( N = 30) for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple models have been developed in an attempt to recreate a pro‐fibrotic environment using the introduction of hepatic stellate cells, which have been acknowledged as the leading scar forming cell type in most liver injuries. [ 32,37 ] It has been frequently found that the greater presence of hepatic stellate cells is commonly linked to the proliferation of hepatoma cells and enhanced tumor metastasis. [ 38,39 ]…”
Section: Liver Anatomy Physiology and Adverse Outcome Pathways Assomentioning
confidence: 99%